CKS1B promotes the progression of hepatocellular carcinoma by activating JAK/STAT3 signal pathway. Issue 4 (4th July 2021) - Liu, Xitao; Zhao, Defang
ABSTRACT: Hepatocellular carcinoma (HCC) is a malignancy of considerable concern due to its continuous increase in morbidity and mortality. This study attempts to identify the molecules that play a key role in the progression of HCC, explore its potential mechanism, and provide more target choices for targeted therapy. Using overexpression plasmid and shRNA, CKS1B was respectively overexpressed and knocked down to explore its biological function roles in HCC progression and development. MTT and colony formation assays showed that knockdown of CKS1B inhibited the survival and proliferation of HCC cell lines (Hep3B and Huh7). The flow cytometry and western blot analysis showed that knockdown of CKS1B significantly induced the apoptosis of Hep3B and Huh7 cells. The wound healing and transwell invasion assays showed that knockdown of CKS1B had a significant inhibitory effect on the migration and invasion of Hep3B and Huh7 cells. These functional tests confirmed that CKS1B acts as an oncogene that regulates the malignant progression of HCC. Moreover, this study also demonstrated that knockdown of CKS1B inhibited the activation of JAK/STAT3 pathway, evidenced by the significantly downregulated p-STAT3 protein expression. Furthermore, knockdown of CKS1B also downregulated STAT3 target genes TIMP-1, Bcl-2 and VEGF, which were involved in controlling cell apoptosis and migration. On the contrary, overexpression of CKS1B caused the completely opposite results. Taken together, CKS1B acts as an oncogene to promote the proliferation and metastasis of HCC cells by activating JAK/STAT3 signaling pathway.